Evaluating the Performance of Calcium Carbide Kiln Dust in Mortar – Initial Study. (2015) - Latif, Masimawati Abdul; Naganathan, Sivakumar; Razak, Hashim Abdul; Mustapha, Kamal Nasharuddin
Abstract: This initial study evaluated the physical properties, setting time, density and compressive strength of Calcium Carbide Kiln Dust (CCKD) as a potential cement alternative for mortar. CCKD is the by-product of Calcium Carbide (CC) production. This by-product leads to environmental pollutions as CCKD has no valuable and beneficial usage, hence it is disposed as landfills. This study explores the possibility of adding CCKD to mortar mixtures by replacing Ordinary Portland Cement (OPC). Six (6) mortar mixtures containing different CCKD replacements up to 40% by weight and one control mortar results are reported. The results indicated that there is a systematic increase in initial and final setting time with the decrease of density and mortar strength. The mixture compressive strength was lower than the control mortar at all ages. It can be concluded that CCKD mortar mixtures may be utilized to compensate setting rate of cement-based materials. However, more research and development, especially on optimum mix design, setting times, early strength, and durability of concrete should be carried out.